THE INFLUENCE OF BEHAVIORAL FEATURES OF THE MANAGERS UPON FINANCING OF THE COMPANIES ADMITTED IN TEHRAN STOCK EXCHANGE - Souri, Farbod (The journal of contemporary issues in business and government, 2021)
One of the most significant duties encountered by the managers of an enterprise is decision-making. Just like other individuals of the society, the managers have specific individual differences, talents, motivations, inclinations and desires and enjoy from different attitudes, knowledge and value system which can be influential upon the financing policies. The present research deals with review of the influence of the managers’ optimism upon the financing policies and its consequences upon the companies admitted in Tehran Stock Exchange Regarding the purpose, this is an applied research and with respect to the execution, it is descriptive-correlational. In line with this goal, the information of 125 companies in Tehran Stock Exchange during a time period of 2015-2019 were studied. In this research, in order to measure the management overconfidence, the three metrics based on the managers’ bias in prediction of the revenue, investment decisions made by the managers and the investment were used. To test the hypotheses, the multivariable regression with combined data were used. The research findings indicated that the managers’ optimistic behavioral features resulted in an increase in managers’ use of financing patterns through the lever of debt in the companies admitted in Tehran Stock Exchange.